Management of horizontal root fractures by fabrication of canine protected occlusion using composite resin - Joo-Hee Shin; Ryan Jin-Young Kim (Korean Academy of Conservative Dentistry, 2012)
Traumatic injuries of the face often involve root fractures especially in anterior teeth. The prognosis and the treatment of the root fracture depend on the extent of the fracture line, general health and patient compliance. This case report outlines a new conservative trial treatment modality to stabilize the maxillary central incisors with horizontal root fracture on the cervical to middle third by fabricating canine guidance to remove loading on the traumatized maxillary central incisors during eccentric movements and thus inducing spontaneous healing of the fractured line between the fragments. Radiographs after thirty months showed adequate healing with no signs of pathological changes including root resorption, ankylosis or displacement. Long term follow-up revealed that vitality, stability and aesthetics were maintained and the patient was satisfied with the outcome.